From Catalyst Coated Membranes to Porous Transport Electrode Based Configurations in PEM Water Electrolyzers. Issue 14 (27th September 2019) - Bühler, Melanie; Holzapfel, Peter; McLaughlin, David; Thiele, Simon
Abstract : So far the superior cell polarization behavior of membrane electrode assemblies (MEAs) using catalyst coated membranes (CCMs) as compared to those using porous transport electrodes (PTEs) was a paradigm in proton exchange membrane water electrolyzers (PEMWEs). However, this paradigm was so far neither systematically investigated nor understood. In this study, we investigate the changes in PEMWE polarization behavior upon gradually changing the MEA from a full CCM toward a full PTE-type configuration. We explain all observed findings based on the idea for a structural model of discontinuous catalyst layers. Our results show, that for current densities above 750 mA cm −2, PTE-based MEAs can result in a better polarization behavior than CCMs. Therefore, the prevailing paradigm was disproved. CCMs showed better kinetics, while PTE-type configurations performed more reproducible than CCMs despite rougher surfaces. Due to the trend of a stabilizing HFR-free cell voltage, an improved mass transport behavior of the PTE-type configurations at high current densities is assumed. Within the error-tolerance, no clear differences between PTE and CCM-based configurations in ohmic resistance could be determined. We conclude that PTE-based configurations for PEMWE, as alternatives to standard CCM-configurations, could be highly important for future manufacturing techniques depending on the application's needs.